Groundwater and soil moisture data collected in the coastal critical zone of the Delmarva Peninsula, United StatesCUAHSI Hydroshare - Dannielle Pratt; Rachel W. McQuiggan; Eva Snell Bacmeister; Amanda Sprague-Getsy; Holly A. Michael (Data in Brief)
Data presented in this paper were collected from three agricultural and three forested sites along the Delmarva Peninsula, United States between March 2021 and July 2024. The six study sites border salt marsh and have experienced agricultural loss or forest loss from marsh migration driven by sea-level rise, saltwater and freshwater flooding events, and droughts. The study sites were subdivided into 4 zones each: healthy, marginal, transitional, and marsh. Hydrological monitoring equipment was installed in each zone to study space-for-time changes from healthy marsh to healthy upland. Groundwater level, conductivity, and temperature; and soil moisture, conductivity, and temperature were measured in each zone in 15-minute intervals to understand changes in the shallow aquifer and root zone soils. These high-resolution measurements capture critical processes in the shallow aquifer and root-zone soils, including shallow soil salinization during storm surges, groundwater salinization during droughts, and aquifer flushing during rainfall events. This data is crucial for understanding the drivers of marsh migration and their associated feedback mechanisms in the coastal critical zone.